Social Conservation of Local Wisdom on Samin Tribes at Kudus Regency Indonesia - Lestari, Eta Yuni; Wijayanti, Tutik (Komunitas, 2020)
Social conservation values are very important to be maintained and preserved. Social conservation values are the source of Indonesians character. Social conservation values comes from the values of local wisdom that exist in each ethnic, and Indonesian community, one of them is the Samin Tribe. This study aims to find the local wisdom values of the Samin community that are threatened with extinction due to modernization. This study uses a qualitative method, with the process of collecting data carried out through interviews with local leaders of the Samin community in Kudus Regency. Interviews were conducted to explore hereditary social activities about beliefs, traditions, social interactions and livelihoods. The results showed that the Samin Community conserved social values in the form of teachings that must be abandoned and teachings that should be done. Some teachings that should not be carried out are prohibitions of slander, greed, irritability, accusation without proof, jealousy, being bad towards others, accusing, stealing, picking or taking something that is still integrated with the main part, finding other people's things. The teaching that must be done is understanding the property itself, being honest, obeying the teachings, and getting along well. The values of the local wisdom of the Samin community can not only be applied to the local people of the Samin tribe, but can be implemented nationally and globally. Globally, the wisdom value of the Samin community can create world peace.